Designing Shopee E-commerce Packaging Using Sarcasm Quotes as a Cleanliness Campaign Weapon to Increase Awareness - Satria Adiyasa*; Iiq Iqoomatussholihah; Ghina Faridah; Nur Azizah Almarwajiah; Muhammad Ahsanul Mukmin; Hafiluddin Ahmad Jailani; Shella Wardhani Putri; Fajar Ciptandi (Universitas Syiah Kuala, 2023)
The accumulation of waste from e-commerce shopping is increasing among the public, especially in Jakarta. Prefer shopping online because e-commerce purchases are they feel to be more effective, can shorten the time, and the price is more affordable, coupled with restrictions on movement space (PPKM) because the COVID-19 pandemic has made people spend a lot of time at home so that there has been a surge in online shopping trends. From trends, it produces e-commerce waste such as cardboard and plastic packing which needs special handling so as not to cause environmental pollution and natural disasters. This study aims to analyze the campaign strategy needed in developing packaging designs by displaying sarcasm-tinged copywriting wrapped in the Shopee e-commerce waste management program. The analytical method used is qualitative with a target of early adulthood (26-35 years) using data collection through observation, interviews, and literature studies, as well as root cause five why analysis benchmarking. The urgency of the idea of this journal is to increase public awareness of e-commerce waste and how to manage it properly. The result of this design is to create a campaign about e-commerce waste through Shopee packaging design using sarcasm copywriting to attract consumers' attention.